Simulasi Interaktif VIRTUAL PLANT Sistem Pengisian Botol Menggunakan Siemens TIA Portal - Yuliati Yuliati; Teofilus Christiawan Loen; Albert Gunadhi; Andrew Joewono; Peter R. Angka; Diana Lestariningsih; Rasional Sitepu (Universitas Muhammadiyah Surabaya, 2026)
Technological developments in the industrial revolution 4.0 era have encouraged the implementation of automation in the industrial sector. This research was conducted using a simulation approach in utilizing Siemens HMI to display a conveyor simulation for a bottle filling machine. This simulation was designed using TIA Portal V17 software and a Siemens S7-1500 PLC as the main controller. The simulated process consists of liquid filling, bottle closing, bottle counting, and interactive visualization of conveyor status. This research aims to develop a Human Machine Interface (HMI) display that can display a production process simulation visually and support virtual monitoring and control of the system through software. The test results show that the simulation successfully displays the filling, bottle closing, and counting processes with an average time of 8.58 seconds for filling, 8.13 seconds for closing. This research is expected to contribute to the development of industrial automation solutions, especially in the implementation of HMI for conveyor systems through simulation. The results of this simulation can be a reference in the design and development of similar automation systems in the future.